Development of a method of absorbed dose on-line monitoring at product processing by scanned electron beam - Pomatsalyuk, R.I.; Shevchenko, V.A.; Tenishev, A.Eh.; Titov, D.V.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2016)
The conditions of the contact-free absorbed dose monitoring at industrial product processing by electron beam
are investigated. The method is based on analysing the collected charge in a stack monitor (SМ) mounted downstream
of irradiated object. Using computer simulation on the basis of a modified transport code PENELOPE-2008,
it is shown that by placing a filter of low-energy electrons before SМ it is possible to obtain the one-to-one correlation
dependence between the monitor charge and absorbed energy of radiation in the processed object. At a certain
surface density of the filter, this dependence takes on the form similar to linear. The possibility to use an air gap
between the object and SМ as such a filter has been demonstrated. For the conditions of radiation plant with an electron
accelerator LU-10 of NSC KIPT, the optimum distance of the SM location has been established. For the practical
range of the electron energy, beam scan width and surface density of the irradiated product, the constants of the
«product absorbed energy-to- SМ charge » linear dependence have been determined. The capability to establish the
average absorbed dose in the object moving trough the irradiation zone on the SM current is shown. The calculation
data are in satisfactory agreement with the results of measurements. Исследованы условия бесконтактного мониторинга поглощѐнной дозы при обработке продукции на
ускорителе электронов. Метод основан на анализе поглощѐнного заряда в пластинчатом мониторе (ПМ),
размещѐнном за облучаемым объектом. С использованием компьютерного моделирования на базе модифи-
цированного транспортного кода PENELOPE-2008 показано, что путѐм размещения перед ПМ фильтра низ-
коэнергетичных электронов можно получить однозначную корреляционную зависимость между зарядом
монитора и энергией излучения, поглощѐнной в обрабатываемом объекте. При определѐнной поверхностной
плотности фильтра эта зависимость становится близкой к линейной. Показана возможность использования в
качестве такого фильтра воздушного промежутка между объектом и ПМ. Для условий радиационно-
технологической установки с ускорителем электронов ЛУ-10 ННЦ ХФТИ установлено оптимальное рассто-
яние размещения ПМ. Определены коэффициенты линейной зависимости «поглощѐнная энергия в объек-
те/заряд ПМ» для практического диапазона значений энергии электронов, ширины развѐртки пучка и по-
верхностной плотности облучаемых объектов. Показана возможность установления по току ПМ усреднѐн-
ного значения поглощѐнной дозы в объекте, перемещаемом через зону облучения с заданной скоростью.
Полученные данные удовлетворительно согласуются с результатами измерений. Досліджено умови безконтактного моніторингу поглинутої дози при обробці продукції на прискорювачі
електронів. Метод заснований на аналізі поглинутого заряду в пластинчастому моніторі (ПМ), розміщеному
за опромінюваним об'єктом. З використанням комп'ютерного моделювання на базі модифікованого транс-
портного коду PENELOPE-2008 показано, що шляхом розміщення перед ПМ фільтра низькоенергетичних
електронів можна отримати однозначну кореляційну залежність між зарядом монітора і поглинутою в обро-
блюваному об'єкті енергією випромінювання. При певній поверхневій щільності фільтра ця залежність стає
близькою до лінійної. Встановлена можливість використання в якості такого фільтра повітряного проміжку
між об'єктом і ПМ. Для умов радіаційно-технологічної установки з прискорювачем електронів ЛУ-10 ННЦ
ХФТІ встановлена оптимальна відстань розміщення ПМ. Визначені коефіцієнти лінійної залежності «погли-
нута енергія/заряд ПМ» для практичного діапазону значень енергії електронів, ширини розгортки пучка і
поверхневої щільності опромінюваних об'єктів. Показана можливість визначення за струмом ПМ усередне-
ного значення поглинутої дози в об'єкті, що переміщується через зону опромінення з наданою швидкістю.
Отримані дані задовільно узгоджуються з результатами вимірювань.